The lived experience of interaction with authority by members of a fringe group (gang) in New Zealand society : an interpretive descriptive analysis : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Manley, Susan Ellen (Massey University, 1995)
This descriptive interpretive study examines the lived experience of interaction with authority by a fringe group (gangs) in New Zealand society. Using the qualitative methodology of Heideggerian Hermeneutic Analysis, the texts from five interviews are analyzed, interpreted and presented. The participants are asked to tell us what has been significant for them as they experience living in the world. Analysis reveals interpretive phenomenological meanings of motivations, actions, strategies and understandings of their responses to interaction with authority. Extensive findings emerge from their stories in the form of five common themes, two relational themes and a constitutive pattern. The five themes include various forms of dominance, violence, betrayal, submission and manifestation of authority. The two relational themes are epitomized by the way in which members of this group are both 'standing in the shadow' and 'standing in the light' of our New Zealand society when they interact with authority. The constitutive pattern found in their stories reveals the need for 'Creating Places' that keep open a future of possibilities for gangs in our society. The experience of gang interaction with authority is embedded in networks of relationships based in the Gang, the family, the community and the culture of our society and uncovers not only how gangs interact with authority, but how authority interacts with gangs. Their stories reveal everyday events that are recognizable, intelligible and tell us not only how gangs organize their everyday world but what it means for them to profoundly be in the world. Understanding this has the effect of creating a place for gangs that is open to possibilities not only for themselves but for society in general.
Keywords: Gangs, New Zealand; Authority